Fostering financially savvy generations: the intersection of financial education, digital financial misconception and parental wellbeing - Senduk, Feibry Feronika Wiwenly; Djatmika, Ery Tri; Wahyono, Hari; Churiyah, Madziatul; Mahasneh, Omar; Arjanto, Paul (Frontiers in Education, 2024)
In today’s technologically advanced era, personal financial competence is critical for successful living, particularly as individuals face increasing complexities in financial decision-making. This study explores the impact of personal financial education on financial management behavior, digital financial misconceptions, and parental well-being among Generation Z in Indonesia. This quantitative study employed Structural Equation Modeling (SEM) to analyze data from 1,843 high school students across Indonesia. The study focused on the relationships between personal financial education, financial management behavior, digital financial misconceptions, and parental well-being. Data were collected through a cross-sectional survey, with instruments designed to measure each of the key variables. The findings reveal that personal financial education significantly influences financial management behavior, which in turn impacts digital financial misconceptions and parental well-being. Moreover, personal financial education directly affects both digital financial misconceptions and parental well-being, with strong indirect effects mediated through financial management behavior. The results underscore the importance of integrating comprehensive financial education into school curricula to enhance financial literacy and management behaviors. By improving financial management skills and reducing digital financial misconceptions, personal financial education can contribute to better financial outcomes and overall well-being for students and their families. This study highlights the need for educational programs that address the specific challenges posed by digital finance, ensuring that Generation Z is well-equipped to navigate the complexities of modern financial environments.